The state of mineralizing properties of the saliva in children with gastroesophageal reflux disease - S. A. Schneider; A. Yu. Saleh; O. V. Denga (Kazimierz Wielki University, 2020)
Gastroesophageal reflux disease (GERD) is one of the most common, potentially dangerous gastrointestinal diseases, which, according to the World Health Organization (WHO), is considered to be a disease of the 21st century. In addition, there is a "rejuvenation" of this nosological form. The frequency of pathology of the digestive system among the pediatric population ofUkraine is the second only to the diseases of the respiratory system. The oral cavity is the beginning of the digestive tract, and its mucous membrane is an important integral component of the system of anatomical and physiological connections of the gastrointestinal tract, and the oral fluid is one of the most important elements that perform the mineralizing function. The authors conducted the investigation to study the mineralizing properties of the saliva in children with GERD, which involved 92 children, of whom 45 children had manifestations of GERD; the remaining 47 were somatically healthy. The content of ionized calcium and inorganic phosphates together, ∆pH, as well as the state of bone metabolism were studied in order to detect a disturbance of the total mineralization of the bone tissue using an ultrasonic densitometer. A decrease in the mineralizing properties of the mixed saliva was found in patients with GERD.